Impaired Control of Brucella melitensis Infection in Rag1-Deficient Mice - Izadjoo, Mina J. (American Society for Microbiology, 2000)
After intranasal inoculation, Brucella melitensis chronically infects the mononuclear phagocyte system in BALB/c mice, but it causes no apparent illness. Adaptive immunity, which can be transferred by either T cells or antibody from immune to naive animals, confers resistance to challenge infection. The role of innate, non-B-, non-T-cell-mediated immunity in control of murine brucellosis, however, is unknown. In the present study, we documented that BALB/c and C57BL/6 mice had a similar course of infection after intranasal administration of 16M, validating the usefulness of the model in the latter mouse strain. We then compared the course of infection in Rag1 knockout mice (C57BL/6 background) (referred to here as RAG-1 mice) which have no B or T cells as a consequence of deletion of Rag1 (recombination-activating gene 1), with infection in normal C57BL/6 animals after intranasal administration of B. melitensis 16M. C57BL/6 mice cleared brucellae from their lungs by 8 to 12 weeks and controlled infection in the liver and spleen at a low level. In contrast, RAG-1 mice failed to reduce the number of bacteria in any of these organs. From 1 to 4 weeks after inoculation, the number of splenic bacteria increased from 2 to 4.5 logs and remained at that level. In contrast to the consistently high numbers of brucellae observed in the spleens, the number of bacteria rose in the livers sampled for up to 20 weeks. Immunohistologic examination at 8 weeks after infection disclosed foci of persistent pneumonia and large amounts of Brucella antigen in macrophages in lung, liver, and spleen in RAG-1, but not C57BL/6, mice. These studies indicate that T- and B-cell-independent immunity can control Brucella infection at a high level in the murine spleen, but not in the liver. Immunity mediated by T and/or B cells is required for clearance of bacteria from spleen and lung and for control of bacterial replication in the liver.